The Evolution of Cultural Relics: Environmental Sculpture of Huai’an in Metaverse - Li, Shifeng; Bunlikhitsiri, Bunchoo; Punthupakorn, Poradee (Journal of Ecohumanism, 2024)
In recent years, with the rapid development of digital technology, cultural have gradually introduced the concept of digital system. Taking the environmental sculpture of Huai’an city as an example, this paper discusses the application of the meta-cosmic digital system in the cultural relics records, and analyzes the significance of this technology for transnational exchanges and mutual learning among civilizations. Through the in-depth study of the management of Huaian environmental sculpture, this paper finds that the digital system of the universe can also realize the real-time recording, virtual display and global sharing of cultural relics, thus providing a new way and method for the protection and inheritance of cultural relics. At the same time, the use of metaso digital system can also promote the innovation and artistic exchange of urban sculpture, and promote the process of mutual learning among civilizations. Therefore, the application of metaso digital system in cultural records has great theoretical and practical significance.